Systematic review and meta-analysis of T1 glottic cancer outcomes comparing CO2 transoral laser microsurgery and radiotherapy - Michael F. Vaculik; Colin A. MacKay; S. Mark Taylor; Johnathan R. B. Trites; Robert D. Hart; Matthew H. Rigby (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The objective of this study is to compare the oncologic outcomes of CO2 transoral laser microsurgery (TLM) and radiotherapy (RT) for treatment of T1 glottic carcinoma. Methods A literature search was conducted in the following databases: Medline/PubMed, Web of Science, EMBASE, and the Cochrane Library. Search results were screened, and publications comparing oncologic outcomes of T1N0M0 glottic carcinoma treated with TLM or RT were included. Data was extracted independently by two authors, and publication quality was graded according to the Oxford Centre for Evidence-based Medicine. Meta-analysis was performed for overall survival, disease specific survival, laryngeal preservation, and local control. Results Sixteen studies were included in the meta-analysis, the majority being retrospective cohort studies with two prospective cohort studies. Included studies were rated as either Level II or III evidence. Meta-analysis favoured treatment with TLM for T1 glottic carcinoma patients for the following outcomes: overall survival (odds ratio [OR], 1.52; 95% confidence interval [CI], 1.07–2.14; P = 0.02), disease specific survival (OR, 2.70; CI, 1.32–5.54; P = 0.007), and laryngeal preservation (OR, 6.31; CI, 3.77–10.56; P < 0.00001). There was no difference in local control between TLM and RT in T1 glottic cancer (OR, 1.19; CI, 0.79–1.81; P = 0.40). Discussion Our study provides a current and thorough comparison of TLM and RT outcomes in T1 glottic carcinoma. Limitations of our study include lack of randomized control trials, and non-randomized allocation of patients to treatment groups. Our meta-analysis suggests that TLM is the superior modality in terms of overall survival, disease specific survival, and laryngeal preservation. Future prospective randomized controlled studies are required for confirming these findings and developing appropriate clinical practice guidelines. Level of evidence 2A; as per the Centre of Evidence Based Medicine.